PERBANDINGAN KUALITAS KARBON AKTIF YANG DIBUAT DARI BATOK KELAPA HIBRIDA DAN BATOK KELAPA DALAM - Tangkuman, Herling D.; Aritonang, Henry F. (Sam Ratulangi University, 2009)
This research was done to compare carbon quality made from hybrid coconut shell and deep coconut shell using direct process from coconut shell to be active carbon at 800- 1200oC temperature. The results shows that active carbon from deep coconut shell was better compared with hybrid coconut shell. Deep coconut shell has: ash content 2,1, water content 3,9, bonding carbon content 98, Iod absorbed ability 904, CTC 54, good galnular, consecutively and hard, whereas hybrid coconut shell has : ash content 12,4, water content 6,8, bonding carbon content 68, Iod absorbeb ability 482, CTC 28, desultory glanular and brittl